KAYISININ ÇÖZELTİ ORTAMINDA KÜKÜRTLENMESİ SIRASINDA KÜKÜRT DÜZEYİNE BAĞLI OLARAK VİTAMİN DEĞERLERİNDEKİ DEĞİŞİMİN BELİRLENMESİ - MUTLU, NAZLI GÜLÜM (Fırat Üniveristesi, 2013)
Malatya yöresine özgü kayısı meyvesinin piyasadaki yerinin korunması, kalite standartlarının yerine getirilmesi bakımından organik tarım ürünlerine olan talebin giderek arttığı günümüz koşullarında alternatif üretim şekillerine gidilmelidir. Bu amaçla çalışmamızda, çözelti ortamında kayısıların daha kısa sürede kükürtlenmesi işleminin iyileştirilmesi ile büyük kapasiteli işletmelerde uygulanabilirliği hakkında bilgi elde etmek amaçlanmıştır. Meyvedeki kükürt düzeyi çözelti ortamında daha rahat kontrol edilebildiğinden, çözelti ortamında kükürtleme işlemi tercih edilmiştir. Kayısıların çözelti ortamında kükürtlenmesi ile eş zamanlı kayısıdaki kükürt düzeyinin bir fonksiyonu olarak vitamin değerlerindeki değişiminin belirlenmesi ile ilgili sınırlı sayıda araştırmaya rastlanmıştır. Bu çalışmada kayısıların kükürtlenmesinde kullanılmak üzere sodyum metabisülfitin farklı konsantrasyonlarında sulu çözeltileri (% 5, % 15, % 20) hazırlandı. Çözelti konsantrasyonunun ve daldırma süreleri değiştirilerek numunelerin absorpladığı kükürt miktarı ölçüldü. Bu bağlamda farklı sodyum metabisülfit konsantrasyonlarında 15, 45, 60 ve 90 dakikalık daldırma sürelerinde kayısı numunelerinin absorpladığı kükürt miktarları ölçüldü. Kayısı numunelerinin kükürt içeriği daldırma süresiyle ve konsantrasyonla doğru orantılı olarak değiştiği gözlendi. Mevcut çalışmada iki farklı cins kayısı türü kullanılarak, kayısı cinsinin kükürt absorplama üzerine etkisi araştırıldı. Hacıhaliloğlu ve kabaaşı kayısı cinsleri araştırmada kullanıldı. Aynı konsantrasyon ve aynı daldırma sürelerinde özellikle yüksek konsantrasyonlarda kabaaşı kayısı türünün daha fazla kükürt absorbe ettiği gözlendi. Ayrıca kayısı numunelerinin kükürt içeriğine bağlı olarak çeşitli vitamin (K1, D2 ve E tokoferol ve tokoferol ) ve yağ asitlerinin değerlerindeki değişimleri incelendi. Kayısı numunelerine bağlı olmaksızın numunelerin kükürt içeriği arttıkça vitamin değerlerinde düşme gözlendi. Dolayısıyla hem çözelti konsantrasyonu hem de daldırma süresi arttıkça vitamin değerlerinde düşme gözlendi. Ayrıca kayısı numuneleri güneşte kurutulduktan sonra kükürt içerikleri ölçüldü. Kuruma esnasında su kaybına bağlı olarak numunelerin kükürt miktarlarında önemli ölçüde artış olduğu gözlendi. Bu çalışmada elde edilen veriler; literatürdeki verilerle uyum içerisinde olduğu görülmüştür. Anahtar Kelimeler: Kayısı, Sodyum metabisülfit çözelti konsantrasyonu, daldırma süresi, vitaminler

In order to maintain the value of apricot grown in the Malatya region in the market and meet quality standards, alternative production methods should be searched in today?s conditions in which the demand for organic agriculture products increases progressively. With this purpose in this study the sulfurization method for apricots in dilute solution of Na2S2O5 was investigated to obtain data that can be used as a base to develop industrial sulfurization method better and in shorter time. The dilute solution of Na2S2O5 was preferred to sulfurize apricots since the level of sulfur in the apricot samples can be controlled more easily in the dilute solutions. To our knowledge there are the limited numbers of research about variations of different vitamins in apricots as a function of sulfur contents. In this study the dilute solution of Na2S2O5 at different concentrations namely 5 %, 15 % and 20 % were prepared and used to sulfurize apricot samples at the same ripeness. In order to determine effect of immersion time and concentration of the dilute solution of Na2S2O5, the absorbed sulfur by apricot samples was measured as functions of the concentrations of Na2S2O5 solutions and immersion times. In this context, the amounts of adsorbed sulfur by apricot samples were measured at the different immersion times namely 15, 45, 60 and 90 minutes at different concentrations of the dilute solution of Na2S2O5. It was observed that the amounts of sulfur contents of the apricot samples varied proportionally with the immersion times and concentrations of the dilute solution of Na2S2O5. In order to determine the effect of apricot species namely hacıhaliloğlu and kabaaşı on the sulfurization in the dilute solution of Na2S2O5, the apricots harvested from the two different species of apricot trees were used in this investigation. It was observed that the apricots picked up from kabaaşı apricot tree at especially at high concentrations of the dilute solution of Na2S2O5 absorbed more sulfur than that of hacıhaliloğlu at the same immersion time and the same concentration. In addition to, the variation of different vitamins (K1, D2 and E) and fatty acid values were examined as a function of sulfur content of the samples. It was observed that the amounts of vitamins decrease with increasing sulfur contents of the apricot samples without depending species of apricots. Therefore, it was determined that amounts of vitamins decrease with increasing concentrations of the dilute solution of Na2S2O5 and thus immersion times. Furthermore, the sulfur contents of apricot samples dried in open air were measured and it was observed that sulfur contents per mass of apricot samples increase with losing moisture contents of the apricot samples since weights of apricot samples substantially decrease with drying time. The results obtained from the present study agree with the data obtained from the previous studies.
Apricot sulfur levels as a function of solution environment during sulfurization determination of changes in values of various vitamins
Keywords: Kimya